Documentary Film Design “Living In The Sunlight” - Tiara - Rengganis; Harry Tjahjodiningrat (Universitas Pendidikan Indonesia, 2021)
The prevalence of serious diseases such as cancer and tumors is currently increasing even in children. Patients with this disease need various forms of support such as family love, parenting patterns, and children's self-motivation to recover. This study aims to make a Documentary Film Living in The Sunlight which explains the relationship between family support and motivation to recover in children with serious illnesses at Al Fatih Shelter House in Bandung. At the pre-production stage, data collection was carried out using an interview and observation approach with a sample of 3 children with foot bone TB disease, brain tumor, Wilms tumor, with an additional instrument in the form of statistical test results to see how much children were motivated by the support of people. old. The results of the study are presented in the form of a documentary that describes the high motivation to recover for the three children with severe illness so that they can return to playing like normal children in general. In addition, feeling happy and happy when being with parents, cheerful, enthusiastic about carrying out daily activities, and not being afraid to carry out a series of treatments, are positive characteristics of children who support their recovery. Meanwhile, other external factors that add to the motivation are the existence of social support in parenting, such as the presence and attention of parents and administrators from the Al Fatih Shelter House in Bandung. Through this documentary, it is hoped that a social message will be conveyed to the audience in general about the importance of being grateful and can move the audience to participate in making donations in various forms to support the needs and healing process of the patient's child.Keywords - Documenteries, Design, Production Film